Hydrographic parameters in Lake Constance in 2010 - Ingeborg Bussmann; Martin Wessels (PANGAEA, 2024)
In the south-eastern part of Lake Constance a deep pockmark, a shallow pockmark station, as well as a reference station have been sampled for dissolved methane concentrations (with water samples) and hydrographic parameters with a Seabird CTD probe. The rosette was located within the pockmark with the help of a horizontal scanning sonar. In April 2010 no methane data are available.
In: Bussmann, I; Wessels, M (2015): Hydrography of water column, methane, and methane oxidation rates at two time series stations in Lake Constance [dataset publication series]. Alfred Wegener Institute - Biological Institute Helgoland, PANGAEA, https://doi.org/10.1594/PANGAEA.854468